Gaya Hidup Nasabah dan Keputusan Dalam Penggunaan Kartu Kredit - Muhammad Fauzan (Faculty of Economic and Business, 2017)
The Achievers Life Style and Decision to Use Credit CardThis study discusses the effect of achievers lifestyle on the decision to use credit card to customers of credit card customers of Bank Mandiri branch Pematangsiantar. The goal is to determine the effect of achievers' lifestyle with the decision to use credit cards to customers of Bank Mandiri credit card users. The number of respondents determined as many as 100 respondents. Sampling procedure is done by purposive sampling that is sampling technique based on credit card user who live in Pematangsiantar city. Mutiple linier regressions are used as technique of analysis. The results showed that the achievers lifestyle variables have a significant influence on the decision to use credit cards. From result of regression analysis known that activity and opinion variable have influence stronger than interest to decision using credit card.DOI: 10.15408/ess.v7i2.4987